Off the page - Picoult, Jodi, 1966-; Leer, Samantha van; Gilbert, Yvonne; Fischer, Scott M. (2015)
"When Delilah is united with Oliver, a prince literally taken from the pages of a fairytale, the line between what is on the page and what is possible is blurred, and all must be resolved for the two to live happily ever after"--
Companion book to: Between the lines.
Keywords: Books and reading -- Juvenile fiction; Fairy tales; Books and reading -- Fiction; Princes -- Fiction; Love -- Fiction